The asymmetric impact of real exchange rate on tourism demand - Yeliz Yalcin; Cengiz Arikan; Nezir Köse (The European Journal of Comparative Economics (EJCE), 2021)
Europe is a notable tourism region and so international tourist arrivals are getting more crucial day by day for attraction center countries. Besides many economic factors, exchange rate is also main economic determining factor of tourism demand. This paper investigates the asymmetric effects of the real exchange rate on tourism demand by utilizing asymmetric VAR methodology for 10 most popular destinations in Europe. According to empirical results, there is a negative relationship between the real exchange rate and tourism demand, with mixed effects for a few countries. The effect of the currency appreciation on the total number of tourist arrivals is more greatly than the currency depreciation for France, Netherlands, Poland and Turkey. Austria, Greece and Italy are also affected asymmetrically from the currency rate in the long term but not short term. The tourist arrivals in Spain, Germany and the UK are not asymmetrically sensitive to exchange rate. The results show that decrease in exchange rate have greater impact on the tourism demand compared to increase in the exchange rate in asymmetrically affected countries.
Keywords: Z32; C32; F3; 330; Real exchange rate; Tourism demand; Asymmetric effect; VAR